Factors Affecting Information Needs of Faculty Members of Teachers Training Institutions of Odisha - Behera, Sangita; Satpathy, Sunil Kumar (DESIDOC Journal of Library & Information Technology, 2014)
Information needs of library users are affected by many factors such as, qualification, sex, age, teaching and research experience, socio-economic background of users, availability of information sources and services in libraries, motivation, professional orientation, and other individual characteristics of the users. The study attempts to identify various factors such as, age, gender, qualification, designation teaching and research experience, and their effect on the information needs of the faculty members of Teachers Training Institutions of Odisha. Survey method with questionnaire techniques was used for collection of data. The findings of the study indicate that the faculty members with higher qualifications visit libraries more frequently, the duration of use of library by a faculty does not have any relationships with his/her designation, faculty with more teaching and research experience make more use of library in terms of frequency of visit to library and duration of use, etc. http://dx.doi.org/10.14429/djlit.34.6762